Proceedings of Second International Conference in Mechanical and Energy Technology ICMET 2021, India - Yadav, Sanjay; Haleem, Abid; Arora, P. K.; Kumar, Harish (Springer Nature Singapore, 2023)
This book presents selected peer-reviewed papers from the International Conference on Mechanical and Energy Technologies, which was held on October 28–29, 2021, at Galgotias College of Engineering and Technology, Greater Noida, India. The book reports on the latest developments in the field of mechanical and energy technology in contributions prepared by experts from academia and industry. The broad range of topics covered includes aerodynamics and fluid mechanics, artificial intelligence, nonmaterial and nonmanufacturing technologies, rapid manufacturing technologies and prototyping, remanufacturing, renewable energies technologies, metrology and computer-aided inspection, etc. Accordingly, the book offers a valuable resource for researchers in various fields, especially mechanical and industrial engineering, and energy technologies.
Redesign and Analysis of Cargo Containers for Delivery Drone Applications -- The Opportunities and Challenges of Implementing Green Internet of Things (IOT) Towards Energy Saving Practices in the Current Environment -- Monitoring of Infrastructure and Development for Smart Cities Supported by IOT Method -- A Review on Various Aerodynamics Control Techniques -- Air Pollution Index Prediction: A Machine Learning Approach -- A Comparative Study of Different IOT Sensors -- Evaluating the Performance of Deep Learning Methods and Its Impact on Digital Marketing -- Effectiveness of Machine Learning Technology in Detecting Patterns of Certain Diseases Within Patient Electronic Healthcare Records -- Sparse Function Learning for Alzheimer's Disease Detection Dependent on Magnetic Characteristics Imaging with Mark Information -- A Study on the Relationship between Cloud Computing and Data Mining in Business Organizations
Keywords: Manufactures; Renewable energy sources; Materials; Nanotechnology